Integrated Action Plan (IAP) for Selected Tribal and Backward Districts Glimpses of Some Projects Taken up under IAP Volume II - Planning Commission (Planning Commission, 2012)
Under the IAP program CEDMAP Anuppur had been appointed as executing agency to provide Computer Training to youth District Anuppur (M.P.). Under this program Janpad Panchayat of concerned villages had provided the list of short listed candidate’s for training in CEDMAP, Anuppur. After that since 01-10-2011 CEDMAP had started the first batch In first financial year target was fixed to trained 250 students, in which 150 candidates have been trained till date. Due to limited seats 50 candidates are in waiting list. After the training of the 1st batch 10 candidates had being selected as Computer Operator in Collector Rate in various Government and Private Organizations.
Planning Commission Government of India
Planning Commission Government of India